Statistical methods for human rights - Asher, Jana; Banks, David L.; Scheuren, Fritz (Springer, 2008)
Human rights issues are shaping the modern world. They define the expectations by which nations are judged and affect the policy of governments, corporations, and foundations. They have set the agenda in prosecutions at the International Criminal Court at the Hague, funding decisions by the International Monetary Fund, and corporate expansion programs by multinationals. Statistics is central to the modern perspective on human rights. It allows researchers to measure the effect of health care policies, the penetration of educational opportunity, and progress towards gender equality. The new wav.